Synthesis of graphene oxide decorated with core@double-shell nanoparticles and application for Cr(vi) removal. Issue 129 (15th December 2015) - Huang, Binyan; Liu, Yunguo; Li, Bin; Zeng, Guangming; Hu, Xinjiang; Zheng, Bohong; Li, Tingting; Jiang, Luhua; Tan, Xiaofei; Zhou, Lu
Abstract : A novel graphene oxide composite, namely Fe3 O4 @SiO2 @ chitosan/GO nanocomposite (MSCG) was synthesized for decontamination of Cr(vi ) from aqueous solution. Abstract : A novel graphene oxide composite, namely Fe3 O4 @SiO2 @ chitosan/GO nanocomposite (MSCG) was synthesized for decontamination of Cr(vi ) from aqueous solution. High-resolution transmission electron microscopy revealed a core@double-shell structure of the nanoparticles with iron oxide as the core, silica as the inner shell and chitosan as the outer shell. The characteristic results of Fourier transform infrared (FTIR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), vibrating sample magnetometry (VSM) and X-ray diffraction (XRD) showed that the Fe3 O4 @SiO2 @chitosan particles were successfully assembled on the surface of the GO layers. The adsorption kinetics followed the pseudo-second-order model and the novel MSCG adsorbent exhibited better Cr(vi ) removal efficiency in solutions at low pH. Thermodynamic parameters revealed that the sorption reaction was endothermic and spontaneous. Moreover, the adsorption capacity was about 90% of the initial saturation adsorption capacity after being used four times. By using a permanent magnet, the recycling process of both the MSCG adsorbents and the adsorbed Cr(vi ) is more economically sustainable. These results suggest that MSCG is a potential and suitable candidate for the preconcentration and separation of Cr(vi ) from wastewater and for the deep-purification of polluted water.